Protective effects of grape seed procyanidin on isoflurane-induced cognitive impairment in mice. (1st January 2020) - Gong, Xiangdan; Xu, Lizhi; Fang, Xin; Zhao, Xin; Du, Ying; Wu, Hao; Qian, Yue; Ma, Zhengliang; Xia, Tianjiao; Gu, Xiaoping
Abstract: Context: Oxidative imbalance-induced cognitive impairment is among the most urgent clinical concerns. Isoflurane has been demonstrated to impair cognitive function via an increase in oxidative stress. GSP has strong antioxidant capacities, suggesting potential cognitive benefits. Objective: This study investigates whether GSP pre-treatment can alleviate isoflurane-induced cognitive dysfunction in mice. Materials and methods: C57BL/6J mice were pre-treated with either GSP 25–100 mg/kg/d for seven days or GSP 100–400 mg/kg as a single dose before the 6 h isoflurane anaesthesia. Cognitive functioning was examined using the fear conditioning tests. The levels of SOD, p-NR2B and p-CREB in the hippocampus were also analysed. Results: Pre-treatment with either a dose of GSP 50 mg/kg/d for seven days or a single dose of GSP 200 mg/kg significantly increased the % freezing time in contextual tests on the 1st (72.18 ± 12.39% vs. 37.60 ± 8.93%; 78.27 ± 8.46% vs. 52.72 ± 2.64%), 3rd (93.80 ± 7.62% vs. 52.94 ± 14.10%; 87.65 ± 10.86% vs. 52.89 ± 1.73%) and 7th (91.36 ± 5.31% vs. 64.09 ± 14.46%; 93.78 ± 3.92% vs. 79.17 ± 1.79%) day after anaesthesia. In the hippocampus of mice exposed to isoflurane, GSP 200 mg/kg increased the total SOD activity on the 1st and 3rd day and reversed the decreased activity of the NR2B/CREB pathway. Discussion and conclusions: These findings suggest that GSP improves isoflurane-induced cognitive dysfunction by protecting against perturbing antioxidant enzyme activities and NR2B/CREB pathway. Therefore, GSP may possess a potential prophylactic role in isoflurane-induced and other oxidative stress-related cognitive decline.